1984
DOI: 10.1177/004728758402300203
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Segmentation of the Tourism Market Using a Benefit Segmentation Framework

Abstract: This study reports an attempt to segment the travel market by showing how different factors influenced choice in different seasons. Results showed that benefits sought for each season differ, and people seeking a combination of benefits during one season may not be the same people seeking the same benefits during another season.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
1
1

Year Published

1995
1995
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(50 citation statements)
references
References 20 publications
3
45
1
1
Order By: Relevance
“…This study has shown that, as Frochot & Morrison (2000) argued, benefit segmentation could be used for development or modifying of vacation packages, and is in line with previous studies (Calantone & Johar, 1984;Woodside & Jacobs, 1985). Also, segmentation based on benefits tourists seek could help destinations coordinate activities of actors along the destination value chain, as well as to create more efficient marketing campaigns.…”
Section: Resultssupporting
confidence: 85%
“…This study has shown that, as Frochot & Morrison (2000) argued, benefit segmentation could be used for development or modifying of vacation packages, and is in line with previous studies (Calantone & Johar, 1984;Woodside & Jacobs, 1985). Also, segmentation based on benefits tourists seek could help destinations coordinate activities of actors along the destination value chain, as well as to create more efficient marketing campaigns.…”
Section: Resultssupporting
confidence: 85%
“…In the past few decades, tourism marketing researchers have carried out various segmentation studies by using observable variables or unobservable variables such as demographic variables (Woodside & Pitts, 1976), travel activities (Tsang, Choi, & Tsang, 1999), benefits sought (Calantone & Johar, 1984;Yannopoulos & Rotenberg, 1999), and motivation (Crompton & McKay, 1997;Nicholson & Pearce, 2000). However, in order to effectively segment tourists in groups to understand and predict travel behaviors, a new construct-lifestyle-has been developed and utilized in marketing research.…”
Section: Introductionmentioning
confidence: 99%
“…The seasonal product meets the seasonal demand, which varies according to the needs, motives and habits by seasons, which leads to the conclusion that tourists are looking for different benefits of the tourism product through the seasons (Capo, Riera Rossello, 2007;Rossello, Riera, Sanso, 2004;Spotts and Mahoney, 1993;Calantone and Johar, 1984). Set of benchmarks must be focused and limited to a certain period of time, but proper performance requires that measurements of performance are time oriented, and not only state oriented, because ignoring the impact of situational context can lead to inaccurate research findings.…”
Section: Temporal Component Of Hotel Performancementioning
confidence: 99%
“…Set of benchmarks must be focused and limited to a certain period of time, but proper performance requires that measurements of performance are time oriented, and not only state oriented, because ignoring the impact of situational context can lead to inaccurate research findings. Calantone and Johar (1984) point out that products and services that have a seasonal character of use require seasonal-based performance research. Accordingly it is necessary to approach the measurement and analysis of hotel performance from different time points/periods, or observe them over time, or seasons.…”
Section: Temporal Component Of Hotel Performancementioning
confidence: 99%